The difference between health education with PowerPoint and booklet media to increase knowledge about the dangers of smoking - Rahmadhani, Suci Nur; Sunarto; Sudiro (Basic and Applied Nursing Research Journal, 2024)
Background: Cigarettes are cylindrical objects that contain many dangerous additives. The danger of smoking is that it can cause perio-dontitis (gums inflammation, pharyngitis (throat infection), laryngitis (infection of the larynx and vocal cords), and bronchitis (infection of the bronchial tubes). Protecting the dangers of smoking can be provided through health education. Health education can be provided using several methods. One of them is the lecture method using interesting media such as PowerPoint and bookletsObjective: To determine the difference in increasing knowledge of the dangers of smoking between the Health Education lecture method with PowerPoint media and booklets. Methods: This study used a quasi-experimental method with a two-group pretest and posttest. The 63 respondents in the sample were di-vided into 31 respondents in the booklet group (B) and 32 respondents in the PowerPoint group (P). The questionnaire contains 15 questions used to measure knowledge of the dangers of smoking.Results: The mean value was 66.34 for the PowerPoint media lecture approach and 76.16 for the booklet media lecture method. The Mann-Whitney test indicated a difference between the two presentations (p = 0.010).Conclusions: There is a difference in increasing knowledge about the dangers of smoking between health education lecture methods with PowerPoint media and booklets.